2020
DOI: 10.1021/jasms.0c00032
|View full text |Cite
|
Sign up to set email alerts
|

PINE: An Automation Tool to Extract and Visualize Protein-Centric Functional Networks

Abstract: Recent surges in mass spectrometry-based proteomics studies demand a concurrent rise in speedy and optimized data processing tools and pipelines. Although several stand-alone bioinformatics tools exist that provide protein−protein interaction (PPI) data, we developed Protein Interaction Network Extractor (PINE) as a fully automated, user-friendly, graphical user interface application for visualization and exploration of global proteome and post-translational modification (PTM) based networks. PINE also support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 115 publications
0
20
0
Order By: Relevance
“…Clustering analysis and network analysis. PCA was performed using the Factoextra package in R. Hierarchical clustering was performed using the pheatmap package in R. Protein network analysis was performed with PINE (22). The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE (68) partner repository with the data set identifier PXD025462.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clustering analysis and network analysis. PCA was performed using the Factoextra package in R. Hierarchical clustering was performed using the pheatmap package in R. Protein network analysis was performed with PINE (22). The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE (68) partner repository with the data set identifier PXD025462.…”
Section: Methodsmentioning
confidence: 99%
“…Genes were considered differentially expressed with an adjusted P value of less than 0.05 and FC of greater than 2. Differentially expressed genes were analyzed using PINE (22). Cell deconvolution analysis was performed with CIBERSORT (70) (cell-type identification by estimating relative subsets of RNA transcripts) using the cell signature file LM22.…”
Section: Cytokine Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the network visualization tool PINE, 24 we also visualized a subnetwork of enriched GO categories/pathway terms to compare the effect of percent CD41+CD42a+ across the 163 significantly expressed protein/gene pairs (see Figure 3). The resulting subnetwork consists of two central nodes for GO categories/pathway terms connected to its associated gene nodes.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Kilanczyk et al have shown that SAMe promotes antioxidant and glutathionylation processes in cholangiocytes that prevent the autoimmune response in patients with primary biliary cholangitis . Finally, several tools extract and visualize protein-centric functional networks, such as PINE, and infer biological functions of uncharacterized proteins, uPE, as defined by the C-HPP, based on gene expression correlation and the PageRank algorithm UPEFinder …”
Section: Highlights From the B/d-hppmentioning
confidence: 99%